2014
DOI: 10.1109/tase.2013.2285813
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Use of Multirobot Production Lines in the Automotive Industry: Detailed System Modeling and Optimization

Abstract: This paper quantitatively reports about potential energy savings on robotic assembly lines for the automotive industry. At first, a detailed system model is described, which improves previously published results by explicitly considering both manipulator and electrical drive dynamics. The model closely captures experimental data in terms of actuation torques and servodrive voltages, which are directly used to derive the plant input power. Two practical methods are then evaluated for reducing the overall energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 23 publications
0
43
0
2
Order By: Relevance
“…This type of optimization, developed in recent times in industrial applications, due to the need to reduce the energy consumption, is found in several studies: T. Mashimo, T. Urakubo and T. Kanade [34]; D. Meike, M. Pellicciari and G. Berselli [35]; O. Wigstrom, B. Lennartson, A. Vergnano and C. Breitholtz [36]; J. Gregory, A. Olivares and E. Staffetti [37]". In these studies are used different algorithms or methods for trajectory planning, including modeling and simulation.…”
Section: Minimum Energy Trajectory Planningmentioning
confidence: 99%
“…This type of optimization, developed in recent times in industrial applications, due to the need to reduce the energy consumption, is found in several studies: T. Mashimo, T. Urakubo and T. Kanade [34]; D. Meike, M. Pellicciari and G. Berselli [35]; O. Wigstrom, B. Lennartson, A. Vergnano and C. Breitholtz [36]; J. Gregory, A. Olivares and E. Staffetti [37]". In these studies are used different algorithms or methods for trajectory planning, including modeling and simulation.…”
Section: Minimum Energy Trajectory Planningmentioning
confidence: 99%
“…The first step of the general workflow of the software approach is the definition of a suitable system model: this is exploited to perform simulations and the analysis of different strategies, through the evaluation of the energy consumption and the dynamic behavior of the mechatronic system [37]. In literature, different approaches are used to build the model; it can be defined through a mathematical formulation and by considering only the main important factors (i.e., basic mathematical model) , or it is possible to also take into account secondary terms that increase the results' precision but on the other hand need more computational efforts (i.e., extended mathematical model) [71][72][73][74][75][76][77]. The availability of software simulation tools allows thus the simple implementation of complex extended models [78][79][80][81] that can describe several physical domains [37,[82][83][84][85].…”
Section: Software: Enhancement Of the Motion Planning Phasementioning
confidence: 99%
“…Operations scheduling is a further approach related to the motion planning modification that can be found in literature, which saves energy by reducing the energy consumption of a single robotic system or a robotic cell [61][62][63][64][65][66][67][76][77][78]88,89,91,92]. In a robotic cell, a robot works synchronously with other robots or mechatronic systems, and the whole work has to be balanced in order to avoid queues.…”
Section: Operations Schedulingmentioning
confidence: 99%
See 2 more Smart Citations